2011
DOI: 10.1063/1.3557395
|View full text |Cite
|
Sign up to set email alerts
|

Electrically detected magnetic resonance in a W-band microwave cavity

Abstract: We describe a low-temperature sample probe for the electrical detection of magnetic resonance in a resonant W-band (94 GHz) microwave cavity. The advantages of this approach are demonstrated by experiments on silicon field-effect transistors. A comparison with conventional low-frequency measurements at X-band (9.7 GHz) on the same devices reveals an up to 100-fold enhancement of the signal intensity. In addition, resonance lines that are unresolved at X-band are clearly separated in the W-band measurements. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Electrical detection of magnetic resonance (EDMR) shows increased sensitivity compared to standard Electron Spin Resonance (ESR), which requires about 10 9 spins per resonance line. In our EDMR studies in X-and W-band cavities [32,33,52], micron scale transistors where formed in 28 Si epi layers. Donor were implanted into transistor channels.…”
Section: Coherence Of Donor Spins In 28-siliconmentioning
confidence: 99%
“…Electrical detection of magnetic resonance (EDMR) shows increased sensitivity compared to standard Electron Spin Resonance (ESR), which requires about 10 9 spins per resonance line. In our EDMR studies in X-and W-band cavities [32,33,52], micron scale transistors where formed in 28 Si epi layers. Donor were implanted into transistor channels.…”
Section: Coherence Of Donor Spins In 28-siliconmentioning
confidence: 99%
“…We have further measured similar devices in a W-band (%100 GHz) cylindrical microwave cavity and have found that the same capacitative shunt design works equally well at the higher microwave frequency. 2 While we demonstrated the suppression of microwave rectification effects with MOSFETs, the use of the shunt capacitor is generally applicable to other transport experiments where microwave irradiation is required. One example is spin-dependent recombination experiments, 1,6-8,25-28 where having a metallic shunt layer covering the device would obstruct the above-band-gap illumination needed for photocarrier generation in this experiment.…”
mentioning
confidence: 97%
“…With the help of the Easyspin toolbox for Matlab [188] the authors were able to simulate the time evolution of the triplet signal. For further characterization of solar cells, new methods such as electrically detected magnetic resonance (EDMR) are under development [189]. EDMR is an ideal technique for any conductive material as magnetic resonance is detected by conductivity changes [190].…”
mentioning
confidence: 99%